MAQÂSHIDÎ INTERPRETATION; A STUDY ON INTERPRETATION OF AHKAM VERSES IN THE APPLICATION OF MAQÂSHID ASY-SYARÎAH - Seroza, Candra Boy; Ridwan, Ahmad Hasan (AKADEMIKA: Jurnal Pemikiran Islam, 2020)
This study explains Maqâshidî Interpretation and its application in interpretation Of Ahkam Verses, and aims to discussion on Maqâshid asy-Syarî’ah and the significance and urgency of Maqâshidî. Maqâshidî's inter-pretation is expected to provide an alternative interpretation in providing solutions for contemporary problematics and reinterpretation of the interpretation formulations that have been out of date. The research method used in this research is qualitative method and analytical descriptive method. This study concludes that The character of Syarî'ah is permanent and governs the whole af'âl al-Mukallaf in every place and time, then the approach or method of maqâshidî interpretation in interpreting Âyât al-ahkâm is a necessity and very imfortant. The discourse of Âyât al-AhKâm interpretation discusses on the place of law formulation against a problem (Fi'l al-Mukallaf). he necessity of interpretation of the approach or method of Maqâshidî interpretation is not only effective in responding to new issues that have never appeared before but also empowered to reinterpret the formulation of interpretations that have not been relevant anymore in the context of the present and the contemporary.Keywords: Maqâshidî Interpretation, Maqâshid asy-Syarî’ah, Âyât al-AhKâm,